Effect of RGD-functionalization and stiffness modulation of polyelectrolyte multilayer films on muscle cell differentiation - Gribova, Varvara (2012)
Skeletal muscle tissue engineering holds promise for the replacement of muscle due to an injury and for the treatment of muscle diseases. Although RGD substrates have been widely explored in tissue engineering, there is no study aimed at investigating the combined effects of RGD nanoscale presentation and matrix stiffness on myogenesis. In the present work, we use polyelectrolyte multilayer films made of poly(L-lysine) (PLL) and poly(L-glutamic) acid (PGA) as substrates of tunable stiffness that can be functionalized by a RGD adhesive peptide to investigate important events in myogenesis, including adhesion, migration, proliferation and differentiation. C2C12 myoblasts were used as cellular models. RGD presentation on soft films and increased film stiffness could both induce cell adhesion, but integrins involved in adhesion were different in case of soft and stiff films. Moreover, soft films with RGD peptide appeared to be the most appropriate substrate for myogenic differentiation while the stiff PLL/PGA films significantly induced cell migration, proliferation and inhibited myogenic differentiation. The ROCK kinase was found to be involved in myoblast response to the different films. Indeed, its inhibition was sufficient to rescue the differentiation on stiff films, but no significant changes were observed on stiff films with the RGD peptide. These results suggest that different signaling pathways may be activated depending on mechanical and biochemical properties of the multilayer films. This study emphasizes the superior advantage of the soft PLL/PGA films presenting the RGD peptide in terms of myogenic differentiation. This soft RGD-presenting film may be further used as coating of various polymeric scaffolds for muscle tissue engineering.